Laser Ablation Generation of Bismuth Selenide Clusters from Mixtures of Elements, Crystalline Bi2Se3, or Thin Films: Laser Desorption Ionization (LDI) and Surface Assisted LDI Time-of-Flight Mass Spectrometry using Graphene and Nanodiamonds - Mandal, Govinda; Mawale, Ravi Madhukar; Gutwirth, Jan; Němec, Petr; Havel, Josef (Journal of the American Society for Mass Spectrometry, 2020)
A bismuth-selenium system from mixtures of the powdered elements in various molar ratios and from Bi2Se3 crystals and/or thin films was studied using laser desorption ionization and surface assisted laser desorption ionization. The BimSen clusters were observed in both positive and negative ion modes, but the mass spectra were more intense, and also a higher number of clusters was formed in the positive ion mode than in the negative mode. The BiSen+ (n = 1-8), Bi2Sen+ (n = 1-5), and Bi3Sen+ (n = 1-6) clusters were detected. Similarly, in the negative ion mode, BiSen- (n = 2-9) and Bi2Sen- (n = 1-2) clusters were observed. In addition, the formation of Bim+ (m = 1-5), Sen+ (n = 1-8), and Sen- (n = 1-7) clusters was also observed. In total, 33 clusters were generated, and 4 new bismuth selenide clusters that have not been reported before (namely, BiSe7+/-, BiSe8+/-, BiSe9-, and Bi2Se5+) were detected. The formation of similar clusters was also observed from bismuth-selenium mixtures and from crystalline Bi2Se3. Furthermore, the Bi2Se3 thin films prepared from a magnetron sputtering technique were also examined via laser desorption ionization. The generation of clusters from the surface of graphene and nanodiamonds was also studied, but no remarkable difference with comparison to the metal surface was observed.
Keywords: bismuth selenides; clusters; chalcogenide glasses; thin films; laser desorption ionization; time-of-flight mass spectrometry